The Meaning of Qur'anic Tabayyun in Relation to Social Media Information Algorithms: A Contextual Tafsir Study of QS. Al-Hujurat, Verse 6 - Lukman Ubaidillah; Amir Mahmud; Nyoko Adi Kuswoyo (Magister Ilmu Al-Qur'an dan Tafsir UINSU Medan, 2026)
Structural poverty among coastal communities in Aceh is not merely caused by economic factors and policy issues, but is also shaped by religious relations and social stratification. This study aims to analyze how the interpretation of religious teachings, particularly through the perspective of the Sociology of the Qur’an, constructs and sustains social stratification that perpetuates structural poverty. The research employs a qualitative method using a thematic interpretation (maudhu‘i) approach to relevant Qur’anic verses, combined with observation and in-depth interviews with coastal communities in Aceh. The findings reveal that hierarchical and fatalistic interpretations of religion tend to reinforce the legitimacy of social inequality, whereby impoverished fishermen accept their condition as destiny. In contrast, religious interpretations oriented toward social justice and a critical work ethic—such as the concepts of khalifah (vicegerency) and ‘adl (justice)—can function as forms of resistance against unequal social structures. In conclusion, the relationship between religion and social stratification is ambivalent: it can serve both as a mechanism for reproducing structural poverty and as a source of liberation, depending on the dominant modes of religious interpretation and practice.